Ayat-Ayat al-Qur’an dalam Suf Healing Method; Pengobatan Alternatif Penderita AIDS ala Muhammad Zuhri - Mardhatillah, Masyithah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
line"> <This paper aims to describe the use of Qur’anic verses in a Suf healing method of the late Muhammad Zuhri at a clinic called Yayasan Barzakh, which was open to any patient including AIDS sufferers. The research examines the profie of both Zuhri and his foundation, the mechanism of healing especially the use of Qur’anic verses in the healing process and the result of the method. Data includes the documentation and interview. The fidings of the research are, fist, Muhammad Zuhri was a local public fiure who was later widely known, while Barzakh Foundation was a nonprofi organization aimed to heal people mentally or physically. Second, Qur’anic verses use exists in his healing method by variety of ways. Third, in the record keeping, it was only one ODHA who totally recovered from AIDS while some others were able to extend the lifetime